Combining selection models and population structures to inform fisheries management: a case study on hake in the Mediterranean bottom trawl fishery - MYTILINEOU, CHRYSSI; HERRMANN, BENT; KAVADAS, STEFANOS; SMITH, CHRIS J.; MEGALOFONOU, PERSEFONI (Mediterranean Marine Science, 2020)
The reduction of juvenile catch and discards are important targets in fisheries policy. This work examines how selection models can predict the size structure (LFD) of discards and landings considering the effects of area, time period, gear and fisher behaviour. Additional exploitation indicators related to the gear used, fisher's selection pattern, and discards were also estimated. The approach is demonstrated in a study concerning hake in the Mediterranean trawl fishery, focusing on high (HRA) and low (LRA) recruitment areas in the Saronikos Gulf (Eastern Mediterranean) during two periods (June, September) using two codends (40 mm square-40S, 50 mm diamond-50D mesh). The predicted discards LFDs revealed generally higher percentages in the HRA in June when using the 50D. The predicted landings LFDs showed higher percentages in the LRA in September for both codends, but undersized hake were always included. LFDs and exploitation indicators indicated that both codends were inappropriate for sustainable fishing of hake in the HRA, where 50D performed worse than the 40S. Fishing with both codends in the LRA in September revealed the lowest discards rates and minimum sizes of landings close to MCRS (minimum conservation reference size). These results can provide information to fisheries management aiming to protect juveniles and reduce discards through spatio-temporal fishing closures.